Legal Regulation of Decentralized Identification Systems in the Context of Digital Sovereignty - Artyshuk-Bereziuk, Larysa (Академічні візії, 2025)
The purpose of this article is to provide a comprehensive examination of the legal regulation of decentralized digital identification models and to determine their role in strengthening the digital sovereignty of the state within the ongoing transformation of the digital legal environment. Research methods. Methods of analysis and generalization of scholarly sources, system-structural and comparative legal analysis, legal modeling, and theoretical interpretation were applied to identify patterns in the development of digital identification and to substantiate directions for improving regulatory frameworks. Results. The evolution of digital identification models was examined, and a transition from centralized registry-based approaches to distributed architectures of trust was established. Key functional characteristics of decentralized identification solutions based on the cryptographic verifiability of digital attributes and enhanced user control over personal data were identified. International and European regulatory approaches to digital identity governance were analyzed, and their influence on the transformation of interactions among the state, citizens, and digital platforms was determined. The implementation of decentralized identification mechanisms was shown to contribute to increased cyber resilience, reduced concentration of personal data risks, and the development of cross-border digital services. Conclusions. Decentralized digital identification systems were shown to constitute a new legal paradigm of digital trust and to serve as an important instrument for strengthening state digital sovereignty. The expediency of shifting legal regulation from technology-oriented approaches toward functional mechanisms that ensure trust and protection of digital rights was substantiated.